Metafiction and Intertextuality in Contemporary Urdu Novel: A study - Dr. Muhammad Daud Rahat (`, 2025)
This study is an attempt to examine the narrative techniques of Metafiction and intertextuality in contemporary Urdu novels, highlighting how these techniques reshape conventional mode of storytelling. Novelists situate narratives within multilayered literary discourse challenging linearity and singleness of the meaning. The masterly use of metafictional devices such as self-reflexivity, narrative intrusion and the questioning of authorial authority foregrounds the contractedness of the fiction itself. The study urges that these narrative techniques reflect broader cultural negotiations in a postmodern context where identity, history and language emerge as contested terrains. The close reading of selected contemporary Urdu novels will enable the study to demonstrate how intertextuality and Metafiction serve as tools for reimagining narrative form, enabling Urdu novel to converse with both its own literary legacy and global postmodern currents. Keywords: Metafiction, Intertextuality, Narrative Technique, Contemporary Fiction